(untitled) (Journal of International Studies, 2024)
The expansion of the British Empire during the 18th and 19th centuries significantly shaped livestock policies and agricultural practices in their colonies. It is argued here that understanding the British colonial experience in Kedah offers valuable perspectives on how responsible and sustainable livestock production can contribute to addressing the challenges of food security around the world. The current academic study employed a historical method and qualitative approach to investigate the impact of British colonial rule on livestock production in Kedah, Malaya, from 1909 to 1940. The study delved into the British efforts to enhance livestock production in Kedah and highlighted the pivotal role played by livestock production in achieving food security, promoting economic growth, and encouraging responsible consumption. Also, the current study revealed the challenges the British faced in animal husbandry activities during this period. The findings demonstrated that the British had successfully developed the livestock sector in Kedah, proven by the increased meat production, livestock numbers, and income. As a result, this historical study provides valuable insights for addressing contemporary global issues related to food security.